2010
DOI: 10.1097/olq.0b013e3181d012e0
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Outcomes of Partner Notification Among Men and Women Recently Diagnosed With Chlamydia and Their Views on Innovative Resources Aimed at Improving Notification Rates

Abstract: The availability of tailored resources may assist in improving partner notification for chlamydia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
43
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 26 publications
1
43
1
Order By: Relevance
“…However, studies suggest that PDPT could result in more partners being treated, and treated earlier. 9 In the ideal world all partners would attend clinical services for testing and treatment, but the reality is rather different. Hence the liberal use of PDPT by many Australian general practitioners, despite the overlying legal cloud and general practitioners' own personal misgivings.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…However, studies suggest that PDPT could result in more partners being treated, and treated earlier. 9 In the ideal world all partners would attend clinical services for testing and treatment, but the reality is rather different. Hence the liberal use of PDPT by many Australian general practitioners, despite the overlying legal cloud and general practitioners' own personal misgivings.…”
mentioning
confidence: 99%
“…While studies suggest that many individuals prefer to tell their partners in person or by telephone, a proportion of individuals prefer email and SMS as it is less confronting or a more convenient alternative. 9,15 New approaches to and greater guidance on partner management are required. Such efforts would translate into a smoother operation and better outcomes for all involved.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 Chlamydia trachomatis (CT) is the most common bacterial sexually transmitted infection (STI) worldwide. 2 Bacterial coinfection by CT in women with a history of HPV infection has been studied as a potential factor that contributes to the development of malignacies and cervical cancer. Some authors 3 have suggested that previous CT infection is associated with a high risk of developing the disease.…”
mentioning
confidence: 99%